2013
DOI: 10.4293/108680813x13693422519910
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Symptoms After Robotic Prostatectomy in Men with Median Lobes

Abstract: Patients with median lobe enlargement of the prostate have different natural history of lower urinary tract symptoms following robotic prostatectomy as compared with patients without this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Shah et al 11 It is interesting that the subscore for storage symptoms also initially increased in both cohorts followed by progressive declines of −16% in NoML and −25% in ML from their respective baselines by 6 months postoperatively. In contrast, there was a continuous and greater improvement in subscores for voiding symptoms in both groups by 6 months postoperatively (−57% in NoML and −68% in ML).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Shah et al 11 It is interesting that the subscore for storage symptoms also initially increased in both cohorts followed by progressive declines of −16% in NoML and −25% in ML from their respective baselines by 6 months postoperatively. In contrast, there was a continuous and greater improvement in subscores for voiding symptoms in both groups by 6 months postoperatively (−57% in NoML and −68% in ML).…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, our study is the largest series to date comparing preoperative and postoperative symptoms in patients with ML who underwent RARP. 5,[9][10][11] Previous studies have not demonstrated differences in the rate of continence at mid-and long-term follow-up between patients with or without ML. Several investigators have shown differences at early follow up which resolved later.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Quantifying OML can be a challenge; there are no standardized criteria for measuring the size or degree of obstruction. This could be due in part to the fact that there is wide variation in the severity and morphology of middle lobe enlargement [15]. One measurement approach that has been shown to correlate well with BOO is intravesical prostatic protrusion (IPP), an ultrasonic measurement of prostatic protrusion into the bladder [1619].…”
Section: Introductionmentioning
confidence: 99%
“…Treating OML can be a challenge. Middle lobe enlargement and the related IPP are associated with a higher risk of urinary retention and a higher failure rate of medical therapy for LUTS due to BPH [15, 19]. There is also a risk of greater surgical difficulty with this anatomy, particularly when the IPP is severe or there is a high bladder neck [21].…”
Section: Introductionmentioning
confidence: 99%